Marketing of non-timber forest products as products from the Protected Forest Management Unit Batutegi, Lampung, Indonesia - Kurniati, Dwi; Hardjanto, Hardjanto; Trison, Soni (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Batutegi PFMU has much potential for NTFPs, which have been developed in coffee, palm sugar, and honey. The marketing of NTFPs needs attention because what often happens is inefficient marketing, so it doesn’t provide additional income for the community. This study aimed to identify marketing channels, functions, and efficiency based on marketing margins, farmers’ share, and profit-to-cost ratio. There are three marketing channels for coffee, two for palm sugar, and three for honey. The marketing functions performed by farmers, collectors, wholesalers, exporters, KUPS, cooperatives, and resellers are exchange, physical, and facilitation functions. Channel 1 palm sugar is an efficient marketing channel with a marketing margin of IDR 13,724.19 per kilogram, a farmer’s share of 100%, a profit ratio of 15.03, and marketing channel 1 honey with a marketing margin of IDR 224,112.70 per kilogram (Trigona honey), and IDR 124,494.35 per kilogram (Cerana and Dorsata honey), a farmer’s share of 100%, and profit ratio of 10.21 (Trigona honey) and 6.47 (Cerana and Dorsata honey).